Використання військового досвіду отримання інформації при розробці правових засад моніторингу в АПК України - Большаков, В.Н. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Рассматривается проблема использования современного военного опыта в правовом регулювании информацоно-поисковой деяльности (мониторинга) в АПК Украины, обоснования его необходимости. In the article is examined the problem of the usage of modern experience in legal control information retrieval system (monitoring) in APK of Ukraine and established it's necessity. In the offered article possibilities of the legal groundwork of monitoring as an instrument of increasing of affectivity in APK of Ukraine are shown.